Dampak Profitabilitas, Leverage, dan Company Size terhadap Praktik Penghindaran Pajak di Perusahaan Teknologi yang Terdaftar di BEI - Luh Ayu Niata Sari; Putu Sri Arta Jaya Kusuma (Jurnal Akuntansi dan Pajak, 2025)
This research examines the influence of profitability, leverage, and firm size on tax avoidance practices. The study centered on 12 manufacturing firms in the technology sector, chosen via purposive sampling, covering the period from 2021 to 2023. The analysis utilized secondary data extracted from yearly financial statements and employed multiple linear regression techniques. Findings reveal a significant positive correlation between profitability and tax avoidance strategies. However, the study found no substantial effect of leverage or firm size on tax avoidance behaviors.